The wetting properties of Langmuir–Blodgett and Langmuir–Schaefer films formed by DPPC and POSS compounds. (July 2019) - Rojewska, M.; Skrzypiec, M.; Prochaska, K.
Highlights: POSS derivatives as modifiers of thin DPPC films. The influence of POSS chemical structure on the wettability of DPPC/POSS films. The effect of transfer pressure and deposition methods on the wetting properties. Estimation of the surface free energy for DPPC, POSS and DPPC/POSS films. Abstract: The possibility of modification of surface wettability is especially desirable in implantology. This effect is achieved by coating a given material with thin films containing nanoparticles of different chemical properties. In recent years, much interest has been paid to supported phospholipid bilayers (SPBs), because they can be exploited in novel biotechnological devices such as biosensors and mimetic membrane–coated implants. In view of the above, we decided to study the modification of wetting properties of phospholipid layer by two types of polyhedral oligomeric silsesquioxanes (POSS) with different functional groups attached to the silica open–cage. The POSS and phospholipid (1, 2-dipalmitoyl-sn-glycero-3-phosphocholine, DPPC) were vertically (Langmuir-Blodgett; LB) and horizontally (Langmuir-Schaefer; LS) deposited on quartz substrates to form a thin layer structure. The advancing contact angles on the modified surface coated with thin films were measured. The surface free energy (SFE) of DPPC, POSS and their mixed DPPC/POSS films was estimated by using Owens-Wendt-Rabel-Käelbe (OWRK) method. It was shown that the chemical structure of POSS used as a modifier influence the wetting properties of modified quartz surface. Incorporation fluoroalkyl-POSS into DPPC monolayer leads to obtaining a more hydrophobic film, while the addition of polyethylene glycol-POSS creates a more hydrophilic film. The transfer of the film with a more condensed structure led to a more hydrophobic material. The deposition technique (horizontal or vertical) had a particular impact on the modification of wettability of quartz surface coated with monocomponent fluoroalkyl-POSS film, whereas for the modification with mixed DPPC/POSS systems the choice of transfer method was not so significant.